2008
DOI: 10.1021/ie0711731
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Biogasoline from Ethanol over Hydroxyapatite Catalyst

Abstract: Plant-derived, dehydrated ethanol was effectively converted to biogasoline in a one-step process on a highly active nonstoichiometric hydroxyapatite (HAP) catalyst. The biogasoline had a research octane number of 99 and comprised chiefly hydrocarbons from C6 to C10 as well as oxygenates not generated in the methanol-to-gasoline (MTG) process using zeolite. To confirm a proposed scheme for the synthesis of gasoline from ethanol over HAP, alcohol conversions were carried out using paired combinations of five dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 64 publications
1
91
0
1
Order By: Relevance
“…Non-biomedical applications of CDHA are similar to those of ACP and HA. Interesting that CDHA was found to possess a catalytic activity to produce biogasoline (Tsuchida et al 2008).…”
Section: Acpmentioning
confidence: 99%
“…Non-biomedical applications of CDHA are similar to those of ACP and HA. Interesting that CDHA was found to possess a catalytic activity to produce biogasoline (Tsuchida et al 2008).…”
Section: Acpmentioning
confidence: 99%
“…The hydroxyapatites, represented by the formula Ca 10−Z (HPO 4 ) Z (PO 4 ) 6−Z (OH) 2−Z ·n(H 2 O); 0 < Z ≤ 1, contain both basic and acidic sites [20]. Notable other examples of the use of hydroxyapatites as catalyst in other gas-phase, base-catalyzed C-C coupling reactions include the Guerbet reaction of ethanol [20][21][22] and the Lebedev ethanol-tobutadiene process [20].…”
Section: Introductionmentioning
confidence: 99%
“…Ndou et al [5] studied EtOH conversion on MgO as catalyst at different temperatures, the reaction did not take place until T> 673.15 K, then a sharp increase in activity is observed and a peak in selectivity appears near 723.15 K, then selectivity falls down at 773.15K, probably because of the departure of molecular H 2 . However, Tsuchida et al [6,9] observed activity at temperatures as low as 545.15 K for advanced Ca/P catalysts. Desorption of hydrogen (R5) should be avoided in our reaction system to prevent the departure of energy-rich th JEEP -19 th -21 st March 2013 -Nancy H 2 from carbon skeleton.…”
Section: Gas Phasementioning
confidence: 99%
“…When vaporized EtOH is contacted to solids at temperatures near 673.15 K, a lot of different products are obtained containing olefins, paraffins, longer alcohols, diolefins, ketones, aldehydes, ethers, etc. Some H 2 is produced and carbonaceous deposits are formed [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation